In vitro and in silico insights into the soybean 15-lipoxygenase inhibition with a new C-geranylated chalcone-based flavanone - Segaran, Raaginie Tamil; Mohd Fadhlizil Fasihi, Mohd Aluwi; Lam, Kok Wai; Siti Nur Aisyah, Mohd Hashim; Syahrul, Imran; Ng, Chean Hui (Springer Science and Business Media Deutschland GmbH, 2025)
2,4,6-trihydroxy-3-geranylacetophenone (tHGA) is an important molecule found in Melicope pteleifolia and has been reported to exhibit numerous pharmacological activities including LOX inhibition. As part of our continuing efort to search for new 15-sLOX inhibitor with better in vitro efcacies, a C-geranylated chalcone-based favanone (8) was synthesized via facile Friedel–Crafts acylation followed by direct C-alkylation. The synthesized favanone was assayed for its in-vitro inhibition against soybean 15-lipoxygenase (15-sLOX); and predicted for its pharmacodynamic and pharmacokinetic properties using docking simulation, SwissADME and PreADMET server. Results indicated that direct C-alkylation on chalcone intermediate using potassium carbonate as base catalyst was possible to establish the conditions that favor the isomerization of chalcone into favanone. The synthesized favanone (8) showed better LOX inhibitory activity (IC50: 1.02±0.15 µM) when compared to our previously reported parent compound tHGA (1, IC50: 23.6±1.7 µM) and its chalcone-based analogue (2, IC50: 15.2±1.2 µM). The (R) enantiomer of favanone (8) showed a good dock score (−9.97 kcal/mol) which interacts with the target enzyme through one hydrogen bonding, and one hydrophobic interaction with iron-binding amino acid (His 499). Molecular dynamics simulation with 100 ns refned and confrmed the docking study result, and the stability of the complex was verifed based on root-mean-square deviation (RMSD), root-mean-square-fuctuation (RMSF), and protein–ligand interaction analyses. The (R) enantiomer of favanone (8) showed stable hydrophobic and hydrophilic contacts in the active site. This study provides insights into the 15-sLOX inhibitory profle of a C-geranylated chalcone-based favanone with an electron withdrawing substituents (-F-) at ring B as potent lead.